High Performance Work System and Organizational Citizenship Behavior in Multinational Companies in Vietnam: the Mediation Effect of Career Success - Giang Thi Huong Vu (DeReMa (Development Research of Management): Jurnal Manajemen, 2018)
In this study, the relationship between high performance work system (HPWS) and organizational citizenship behavior (OCB) in multinational corporations (MNCs) in Vietnam, a fast-developing country with highly economic growth in Asia, was investigated. Besides, the underlying mechanism of this relationship was also explored. From the social exchange approach, an underlying mediated mechanism of career success in the relationship between HPWS and OCB was hypothesized. Data collected from individual employees working in multinational companies in Vietnam was used to test the hypotheses. The research findings supported the partial mediating role of career success in the positive relationship between HPWS and OCB. In addition, research implications as well as suggestions for future research were also presented. Bahasa Indonesia Abstrak: Dalam studi ini, hubungan antara high performance work system (HPWS) dan organizational citizenship behavior (OCB) di multinational corporations (MNC) di Vietnam, negara cepat berkembang dengan pertumbuhan ekonomi yang sangat tinggi di Asia, ditelliti. Selain itu, mekanisme yang mendasari hubungan ini juga dieksplorasi. Dari pendekatan pertukaran sosial, mekanisme mediasi yang dimediasi dari kesuksesan karir dalam hubungan antara HPWS dan OCB dihipotesiskan. Data yang dikumpulkan dari masing-masing karyawan yang bekerja di perusahaan multinasional di Vietnam digunakan untuk menguji hipotesis. Temuan penelitian mendukung peran mediasi parsial dari kesuksesan karir dalam hubungan positif antara HPWS dan OCB. Selain itu, implikasi penelitian serta saran untuk penelitian masa depan juga disajikan.